Erratum To: Translational efficiency across healthy and tumor tissues is proliferation‐related - Hernandez‐Alias, Xavier; Benisty, Hannah; Schaefer, Martin H; Serrano, Luis (Molecular systems biology, 2021)
Graphical Abstract